Learning Futures Consciousness: An integrative review - Koch, Merlijn J.; Sools, Anneke M.; Spaas, Godelieve H.J.; Westerhof, Gerben J. (Futures : the journal of policy, planning and futures studies, 2025)
This study presents an integrative literature review of Futures Education to analyze and synthesize fragmented knowledge on learning Futures Consciousness (FC)—the capability to envision and critically reflect on possible futures. As an essential competency for addressing complex societal challenges, FC also enhances individual agency, well-being, and collective engagement. Using the 3-P model, the framework systematically analyzes how contextual (Presage), processual (Process), and outcome-related (Product) factors shape the development of FC in formal and informal educational settings. The findings reveal critical gaps in Futures Education research, including the underrepresentation of dimensions of FC, such as "Concern for Others," limited understanding of contextual influences, and the lack of systematic evaluation of challenges encountered in the learning process. Additionally, the roles of educators and the impact of diverse learner backgrounds remain underexplored. This study highlights the need for future research to clearly define intervention contexts, goals, participant diversity, learning processes, and durations. The framework of this study serves as a lens for advancing research, educational design, and evaluation in Futures Education. By highlighting critical gaps and areas for improvement and fostering meaningful exchange on learning FC, it facilitates the development of more effective educational programs, equipping individuals to navigate uncertainty and drive meaningful societal transformation.